O exercício da democracia direta no Brasil: condições, possibilidades e uma proposta de recall - Carvalho, Erick Beyruth de (2018)
The purpose of this study is to analyze the exercise of popular sovereignty in Brazil through the plebiscite, referendum, initiative and recall, without forgetting, however, other mechanisms constitutionally foreseen in the administrative scope – participatory budget and public hearing – and in the jurisdictional scope – popular action, allegation of noncompliance with fundamental precept and writ of injunction. The objective is to investigate the causes of the little use of the mechanisms of semi-direct democracy in Brazil, foreseen in article 14 of the Federal Constitution of 1988, as well as to propose alternatives to expand its use. The investigation is relevant because, faced with the crisis of the western democracies, characterized by the breach of confidence in political parties, the need arises to equip the citizens with instruments that allow them to participate in the political life of the State, aiming at legitimizing and exercising political control on decisions of State and Government. The analysis will be carried by the regulation of semi-direct democracy in the Federal Constitution of 1988 and in the main legislation, making a parallel with other Latin American Constitutions that arise in a historical context of redemocratization